2014
DOI: 10.1177/0194599814522413
|View full text |Cite
|
Sign up to set email alerts
|

Vocal Cord Paralysis and Dysphagia after Aortic Arch Reconstruction and Norwood Procedure

Abstract: Objectives Determine the incidence of vocal cord paralysis and dysphagia after aortic arch reconstruction including Norwood procedure. Setting Tertiary Children’s Hospital Study Design Retrospective cohort. Methods Database/chart review of neonates requiring Norwood or arch surgery between January 2005 through December 2012. Demographics, postoperative vocal cord function, dysphagia, need for gastrostomy tube and/or tracheotomy, and long-term follow-up were reviewed. Results One hundred fifty-one conse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
39
1
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(46 citation statements)
references
References 25 publications
(74 reference statements)
4
39
1
2
Order By: Relevance
“…Because of the retrospective nature of the study, it is impossible to determine whether cardiac surgery or stroke led to dysphagia in some of these patients, unrelated to their PHACE syndrome diagnosis. The cardiac literature supports an incidence of dysphagia in approximately 18% to 57% of children after cardiac surgery, depending on the specific procedures that were performed . This is often attributed to prolonged ventilation or damage to the recurrent laryngeal nerve during surgical repairs, but the fact that posterior fossa abnormalities occurred in 44% of our patients with dysphagia (4/9) may support the theory that abnormal neurodevelopment is contributory in patients with PHACE syndrome as well.…”
Section: Discussionsupporting
confidence: 64%
“…Because of the retrospective nature of the study, it is impossible to determine whether cardiac surgery or stroke led to dysphagia in some of these patients, unrelated to their PHACE syndrome diagnosis. The cardiac literature supports an incidence of dysphagia in approximately 18% to 57% of children after cardiac surgery, depending on the specific procedures that were performed . This is often attributed to prolonged ventilation or damage to the recurrent laryngeal nerve during surgical repairs, but the fact that posterior fossa abnormalities occurred in 44% of our patients with dysphagia (4/9) may support the theory that abnormal neurodevelopment is contributory in patients with PHACE syndrome as well.…”
Section: Discussionsupporting
confidence: 64%
“…We also evaluated for the presence of vocal cord palsy postoperatively, as this is a known complication of cardiac surgery due to mechanisms including injury to the recurrent laryngeal nerve and trauma secondary to intubation, and this in turn is associated with feeding difficulties, poor growth, and need for GT placement (Einarson & Arthur, 2003; Hill et al, 2014; Pham et al, 2014; Sachdeva et al, 2007). The reported incidence of vocal cord palsy in children undergoing cardiac surgery varies from 1.7% to 8% and is associated with lower gestational age, lower birth weight, and lower surgical weight (Carpes et al, 2011; Dewan, Cephus, Owczarzak, & Ocampo, 2012; Strychowsky, Rukholm, Gupta, & Reid, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Several previous studies have noted that patients with diagnosis of hypoplastic left heart syndrome (Davis et al, 2008; Golbus et al, 2011; Kelleher, Laussen, Teixeira-Pinto, & Duggan, 2006) and postoperative vocal cord paralysis (Jadcherla et al, 2009; Pham, Connelly, Wei, Sykes, & O’Brien, 2014) are more likely to require nasogastric or gastrostomy feeds at discharge. One study of 465 infants with single ventricle heart defects found that longer periods of intubation are associated with tube feeding requirement at discharge (Hill et al, 2014), though no other studies have been done to corroborate this finding.…”
Section: Purposementioning
confidence: 99%
“…Vocal fold paralysis can be congenital or acquired; etiologies include iatrogenic, idiopathic, neurologic, and traumatic causes . Unilateral vocal fold paralysis is considered the most common neurologic disorder of the larynx and is frequently caused by intubation or neonatal cardiothoracic surgery . The diagnosis of vocal fold paralysis can be made via flexible fiberoptic endoscopy in the office or at the bedside, or by direct laryngoscopy in the operating room …”
Section: Introductionmentioning
confidence: 99%